In vitro synergistic efficacy of nystatin combined with geraniol against Candida albicans and Candida glabrata biofilm on acrylic resin - Pesee, Siripen; Chaimueang, Chutikarn; Ngamjaroen, Supalux; Satthawong, Pornraphat; Mingkwan, Manita; Suniwatcharanupong, Wipada (Science, Engineering and Health Studies, 2025)
Candida albicans and Candida glabrata predominate in the oral cavities of elderly people with denture stomatitis. Prolonged nystatin treatment can alter the surface properties of acrylic resin, while geraniol can inhibit Candida biofilm without affecting the surface roughness or color of the acrylic resin. This study investigated the efficacy of nystatin/geraniol combinations against C. albicans and C. glabrata biofilms on acrylic resin. Checkerboard assay revealed synergistic activity of nystatin/geraniol combinations. The minimum biofilm eradication concentration (MBEC) and efficacy against Candida biofilm were evaluated by crystal violet assay. The MBEC90 of nystatin against C. albicans and C. glabrata biofilms was 55 and 131 μg/mL, respectively. The MBEC90 of geraniol against C. albicans and C. glabrata biofilms was 330 and 45,367 μg/mL, respectively. A significantly higher percentage of C. albicans biofilm reduction was observed when combining nystatin at 0.25 MBEC with geraniol at 1 MBEC (70.89%) (p<0.05), compared to geraniol monotherapy (42.35%). However, the percentage of C. glabrata biofilm reduction at sub-inhibitory concentrations did not differ from single-agent treatment. In conclusion, nystatin/geraniol combinations had a synergistic effect against C. albicans and C. glabrata, and combinations at sub-inhibitory concentrations can diminish the biomass of Candida biofilms on acrylic resin.